Urgensi Pendidikan Moral dan Akhlak Pada Anak Usia Dini - Ainul Hasanah ('Anil Islam: Jurnal Kebudayaan dan Ilmu Keislaman, 2015)
Morality is fading amid the current association is increasingly free and unimpeded. Therefore, moral education and character urged to continue to be encouraged, especially in early childhood. Interest held education, one of which, is to print the students moral and good morals. However, moral and character education is not enough to just theory, but it requires a model or example that can give you an example. The existence of good examples is essential in the process of moral education and akhlakul karimah for early childhood, because young children have a tendency to imitate the attitudes and behavior of others than to listen to, especially the people around him, such as parents, teachers, and peers. A good model and could be a harbinger in giving the example of the attitude and behavior of the Prophet SAW. Some attitudes and behavior that can be implanted in early childhood: honest, trustworthy, mutual help, respect your parents and others, and generous. To inculcate attitudes and behavior, can be done by giving keteleadan, habituation, and tells the story of a figure that can be emulated and replicated.